Pelaksanaan Pemeriksaan Setempat Dalam Penyelesaian Perkara Perdata Permohonan Pengampuan Di Pengadilan Negeri Malang Kelas IA - Diny Utari, Nathaza; Purwanto, Aldira Mara Ditta Caesar (Lex Stricta : Jurnal Ilmu Hukum, 2025)
On-site inspections are a supporting instrument of evidence that allows judges to see the subject matter of the case firsthand. In practice, these inspections are not only applied to civil lawsuits, but also to guardianship cases. The purpose of guardianship is to protect the civil rights of adults who are deemed legally incompetent. One example is case No. 156/Pdt.P/2024/PN Mlg. Although the applicant had fulfilled the evidence requirements under Article 164 of the HIR and Article 1866 of the Civil Code, the judge still recommended an on-site inspection because the available evidence was deemed insufficient to form a legal conviction. This study uses an empirical method through interviews with judges and court clerks at the Malang Class IA District Court. The results of the study show that on-site inspections serve to directly confirm the facts of the prospective ward's condition and strengthen the written evidence. These findings confirm that although it is not classified as formal evidence, on-site inspections play an important role in ensuring the objectivity of guardianship appointments and protecting vulnerable groups in accordance with the principles of justice and legal certainty.